2012
DOI: 10.1007/s12253-012-9497-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of SPARC Protein Expression in the Progress of Gastric Cancer

Abstract: We aimed to investigate the expression of SPARC (secreted protein, acidic and rich in cysteine) in gastric cancer and its relationship with tumor angiogenesis and cancer cells proliferation. Protein expression of SPARC, VEGF, CD34 and Ki-67 in 80 cases of gastric cancer and 30 cases of normal gastric tissue was evaluated by immunohistochemistry. CD34 staining was used as an indicator of microvessel density (MVD). Ki-67 labeling Index (LI) indicated cancer cells proliferation. Statistical analysis was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
5
26
0
Order By: Relevance
“…The results of the present study demonstrated that SPARC mRNA expression levels were higher in gastric cancer tissues than in adjacent normal mucosa, which is in line with the results of previous studies (17,21). In addition, through univariate and multivariate analyses of potential prognostic factors using Cox proportional hazards models, high SPARC expression was revealed to be a significant predictor of poor survival in patients with stage II/III Table II.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present study demonstrated that SPARC mRNA expression levels were higher in gastric cancer tissues than in adjacent normal mucosa, which is in line with the results of previous studies (17,21). In addition, through univariate and multivariate analyses of potential prognostic factors using Cox proportional hazards models, high SPARC expression was revealed to be a significant predictor of poor survival in patients with stage II/III Table II.…”
Section: Discussionsupporting
confidence: 91%
“…However, previous studies have reported that high SPARC gene expression is associated with the depth of tumor invasion of stage I-IV gastric cancer (25), lymph node metastasis in esophageal cancer (26), tumor size, degree of differentiation, depth of invasion, vascular invasion, lymph-node metastases, distant metastases and TNM stage in gastric cancer (16,17).…”
Section: Multivariate Analysis --------------------------------------mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, function prediction of SULF1 and CTHRC1 revealed that these proteins were mainly involved in ECM organization and constituent, transmembrane receptor protein serine/threonine kinase, FGF receptor, TGF beta receptor and Wnt receptor signaling pathway, angiogenesis, fibrinolysis, regulation of immune, and VEGF production such as SPARC, COL1A1, COL1A2, COL3A1, COL5A2, COL15A1, ASPN, VCAN, TNFSF4, FAP, POSTN, THBS2, THBS1, SULF2, SULF1, FN1, and LUM. Previous studies have reported that SPARC [37,38], COL1A1, COL1A2 and COL3A1 [39,40], POSTN [41], THBS1 [42], and SULF2 and SULF1 [29] were related to tumor stage and metastasis in GC. Though CTHRC1 had no annotated functions, it shared protein domains with collagen proteins and has been reported to be associated with metastasis in GC [21].…”
Section: Discussionmentioning
confidence: 98%
“…In GC tissues, SPARC expression disappeared in cancer cells but localized in stromal cells surrounding the cancer (13,14). However, the relationship between SPARC expression and clinicopathological factors of GCs is controversial.…”
Section: Introductionmentioning
confidence: 99%